Large Sea Surface Temperature, Salinity, and Productivity‐Preservation Changes Preceding the Onset of the Messinian Salinity Crisis in the Eastern Mediterranean Sea. Issue 2 (9th February 2019) - Vasiliev, Iuliana; Karakitsios, Vasileios; Bouloubassi, Ioanna; Agiadi, Konstantina; Kontakiotis, George; Antonarakou, Assimina; Triantaphyllou, Maria; Gogou, Alexandra; Kafousia, Nefeli; de Rafélis, Marc; Zarkogiannis, Stergios; Kaczmar, Fanny; et al.
Abstract: The Messinian Salinity Crisis (MSC; 5.97–5.33 Ma) is an enigmatic episode of paleoceanographic change, when kilometer‐thick evaporite units were deposited in the Mediterranean basin. Here we use geochemical (biomarker and isotope) data to reconstruct sea surface temperature, salinity, and productivity‐preservation changes in the Mediterranean basin just before the MSC. The proxy data indicate that the Mediterranean Sea was significantly saltier and colder between 6.415 and 6.151 Ma, than between 6.151 and 5.971 Ma. Salinity decrease at 6.151 Ma seems to be a relatively fast event just preceding the inception of a warming phase that lasted almost uninterrupted until the MSC onset. The water exchange with the Paratethys could have caused, along with the African rivers, an increased freshwater supply, resulting in normal marine Mediterranean waters between 6.151 and 5.971 Ma, despite the severe restriction of marine connections with the Atlantic at that time. Sea surface temperature changes determined a sharp drop in productivity and/or preservation of organic matter, marked by deposition of calcareous marls. Productivity and preservation were relatively high and constant until 6.01 Ma. Afterward, increased influx of terrestrial organic matter and probably enhanced water column stratification prevailed. Around 5.971 Ma, modifications in aquatic versus terrestrially derived biomarkers indicate changes in organic matter influx at the MSC onset. Plain Language Summary: More than five million years ago, the Mediterranean Sea underwent astonishing changes in its hydrological budget leading to the formation of hypersaline water bodies and the deposition of a more than 1, 000‐m salt giant. The way toward the hypersaline conditions of the Messinian Salinity Crisis (5.97–5.33 Ma) was marked by gradual closure of Mediterranean oceanic seaways. Data reveal that the Mediterranean Sea was 8‰ saltier and, in average, 1.2 °C colder between 6.415 and 6.151 Ma, than between 6.151 and 5.971 Ma. At 6.151 Ma, a salinity decrease from 47‰ toward normal marine of 39‰ was a fast event just preceding the inception of a warming lasting almost uninterrupted until the Messinian Salinity Crisis onset. Key Points: Mediterranean Sea was significantly saltier and colder between 6.415 Ma and 6.150 Ma, than between 6.150 and 5.971 Ma A salinity decrease at 6.150 Ma seems to be a fast event just preceding the inception of a warming phase lasting until the MSC onset Paratethys contributed to increasing freshwater supply from African rivers leading to normal marine Mediterranean between 6.150‐5.971 Ma